2018
DOI: 10.1186/s12889-018-5658-4
|View full text |Cite
|
Sign up to set email alerts
|

The Smart City Active Mobile Phone Intervention (SCAMPI) study to promote physical activity through active transportation in healthy adults: a study protocol for a randomised controlled trial

Abstract: BackgroundThe global pandemic of physical inactivity represents a considerable public health challenge. Active transportation (i.e., walking or cycling for transport) can contribute to greater total physical activity levels. Mobile phone-based programs can promote behaviour change, but no study has evaluated whether such a program can promote active transportation in adults. This study protocol presents the design and methodology of The Smart City Active Mobile Phone Intervention (SCAMPI), a randomised control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…The study was approved by the regional research ethics committee in Stockholm (January 11, 2017: 2016/2403-31 and June 30, 2017: 2017/1373-32) and registered at ClinicalTrials.gov [NCT03086837]. Details on the development of the app and design of the SCAMPI trial are published elsewhere [ 17 ]. The study is reported according to the Consolidated Standards of Reporting Trials of Electronic and Mobile Health Applications and onLine Telehealth (CONSORT-EHEALTH) statement [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was approved by the regional research ethics committee in Stockholm (January 11, 2017: 2016/2403-31 and June 30, 2017: 2017/1373-32) and registered at ClinicalTrials.gov [NCT03086837]. Details on the development of the app and design of the SCAMPI trial are published elsewhere [ 17 ]. The study is reported according to the Consolidated Standards of Reporting Trials of Electronic and Mobile Health Applications and onLine Telehealth (CONSORT-EHEALTH) statement [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, baseline measures of PA (using the wGT3X-BT accelerometer [ActiGraph LLC]) as well as AT (measured through the TravelVu app [Trivector AB], standard version) were assessed simultaneously during 7 consecutive days. The details of the TravelVu app have been provided in the study protocol [ 17 ]. Briefly, the app passively collected data using GPS coordinates and presented total and mode-specific travel minutes per day (for walking, cycling, car, train, ferry, or bus).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…by taking care of CO2 level reduction), green areas such as parks, waste management, public transport (Bell et al, 2018), energy (Pan & Cheng, 2018), quality of residents' life (Chan & Marafa, 2018;Calderón et al, 2018;D' Aniello et al, 2018) (e.g. taking care of health (Ek et al, 2018)) and sound environment (Kang et al, 2018) which influences the comfort of life of urban community. According to Chen and Lin (2019) smart city architecture takes into account 20 areas including in particular information infrastructure based on ICT, artificial intelligence, the IoT or solutions based on a cloud and fog computing (Du et al, 2019;Lytras et al, 2019;Milošević et al, 2019;Sánchez-Teba & Bermúdez-González, 2019), e-administration, social insurance, intelligent transportation (Suryanegara et al, 2019), e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The high prevalence of smartphone use provides novel possibilities to enhance health service delivery [19]. For instance, smartphone technology offers a cost-effective platform for distribution of evidence-based health information and behavioral change interventions [20,21]. Smartphones are found to be particularly suitable for implementation of patient-centred interventions and enhancement of patient self-management capabilities [22,23].…”
Section: Introductionmentioning
confidence: 99%